Surveillance, maintenance and diagnosis of flood protection dikes - Mériaux, Patrice (éditions Quae, 2007)
This technical handbook is intended for the personnel of companies or organisations involved in the management of dikes designed to provide protection against flooding caused by a rise in river levels. Written for engineers and technicians, its aim is to increase understanding of: â€" How dike systems work. â€" The risks faced. â€" Surveillance and maintenance operations. It also aims to explain the reasons for and describe the work to be done to ensure the long-term future and safety of such structures, given water resource legislation in France. Produced upon the initiative of the French Ministry of the Environment (water resources department), this book was written by Cemagref, under the guidance of, and with contributions from, a working party.